In-depth investigation of genome to refine QTL positions for spontaneous sex-reversal in XX rainbow trout - Audrey Dehaullon; Clémence Fraslin; Anastasia Bestin; Charles Poncet; Yann Guiguen; Edwige Quillet; Florence Phocas (PLoS ONE, 2025)
Sex determination is a flexible process in fish, controlled by genetics or environmental factors or a combination of both depending on the species. Revealing the underlying molecular mechanisms may have important implications for research on reproductive development in vertebrates, as well as sex-ratio control and selective breeding in fish. Phenotypic sex in rainbow trout ( Oncorhynchus mykiss ) is primarily controlled by a XX/XY male heterogametic sex determination system. Unexpectedly in genetically XX all-female farmed populations, a small proportion of males or intersex individuals are regularly observed. Spontaneous masculinisation is a highly heritable trait, controlled by minor sex-modifier genes that remain unknown, although several Quantitative Trait Loci (QTL) were detected in previous studies. In the current work we used genome-based approaches and various statistical methods to further investigate these QTL. DNA markers that were previously identified in a French commercial population on chromosomes Omy1, Omy12 and Omy20 were validated in six different farmed trout populations. Functional candidate genes that may be involved in spontaneous masculinisation by reducing germ cell proliferation and repressing oogenesis of XX-rainbow trout in the absence of the master sex determining gene were identified. In particular, syndig1 , tlx1 and hells on Omy1, as well as khdrbs2 and csmd1 on Omy20 deserve further investigation to validate their potential sex-modifier roles as well as their interaction with rearing temperature. Those findings could be used to produce all-female populations that are preferred by farmers due to a delayed maturation of females and higher susceptibility of male trout to diseases.